2020
DOI: 10.1016/j.bmc.2020.115401
|View full text |Cite
|
Sign up to set email alerts
|

Rational modifications, synthesis and biological evaluation of new potential antivirals for RSV designed to target the M2-1 protein

Abstract: Marcella 2020. Rational modifications, synthesis and biological evaluation of new potential antivirals for RSV designed to target the M2-1 protein. Highlights• Rational modifications on a zinc-ejecting anti-RSV scaffold.• Synthesis of novel analogues to explore antiviral SARs.• New inhibitors of RSV replication identified.• Molecular dynamics and molecular docking studies on the RSV M2-1 protein. AbstractRespiratory syncytial virus (RSV) is the main cause of lower respiratory tract diseases in infants and youn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…The best compound 54 (Figure ) exhibited an IC 50 of 6 μM in HEp-2 cells infected with a luciferase-expressing RSV. Five years later, the same authors identified compound 55 (Figure ) (EC 50 = 4.4 and 1.3 μM on RSV A and B, respectively), which differed from the hit 54 due to the replacement of the benzyl ring with a phenyl moiety . Docking studies were conducted on the tetrameric crystal structure of M2-1 protein in complex with the interaction domain of P (PDB: 6G0Y, released in 2018) which led to a refinement of the binding mode of this series of dithiocarbamate derivatives.…”
Section: Inhibitiors Of the Replication Complexmentioning
confidence: 99%
See 1 more Smart Citation
“…The best compound 54 (Figure ) exhibited an IC 50 of 6 μM in HEp-2 cells infected with a luciferase-expressing RSV. Five years later, the same authors identified compound 55 (Figure ) (EC 50 = 4.4 and 1.3 μM on RSV A and B, respectively), which differed from the hit 54 due to the replacement of the benzyl ring with a phenyl moiety . Docking studies were conducted on the tetrameric crystal structure of M2-1 protein in complex with the interaction domain of P (PDB: 6G0Y, released in 2018) which led to a refinement of the binding mode of this series of dithiocarbamate derivatives.…”
Section: Inhibitiors Of the Replication Complexmentioning
confidence: 99%
“…Five years later, the same authors identified compound 55 (Figure 17) (EC 50 = 4.4 and 1.3 μM on RSV A and B, respectively), which differed from the hit 54 due to the replacement of the benzyl ring with a phenyl moiety. 141 Docking studies were conducted on the tetrameric crystal structure of M2-1 protein in complex with the interaction domain of P (PDB: 6G0Y, released in 2018) which led to a refinement of the binding mode of this series of dithiocarbamate derivatives. Therefore, the benzothiazole moiety of 55 interacted with Lys18 A through a π-bond with the sulfur atom pointing toward the oxygen of the Gly18 A backbone.…”
Section: ■ Inhibitiors Of the Replication Complexmentioning
confidence: 99%
“…Moreover, to the best of our knowledge, the employment of N -sulfonyltriazoles in C–S bond forming cascades may be possible only by the use of very expensive Rh catalysts. 30,31 It is worth mentioning that the structural analogues of the obtained products, containing benzimidazole and benzothiazole units, have been shown to exhibit fungicidal, 32 antiviral, 33 and anticancer 34 activities (Scheme 1D).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, over the last few years, some improved procedures based on a simple reaction of a free piperazine with halogenated reagents were published. Although yields were somehow improved, syntheses still feature some particular issues such as the usage of chlorinated solvents [18][19][20], multistep isolation/purification process often including column chromatography [18,19,[21][22][23][24][25] or disadvantageous atom economy when the usual excess of piperazine must be used [3,19,[23][24][25].…”
Section: Introductionmentioning
confidence: 99%